Invisible spaces: variegated geographies of waste in China - Inverardi-Ferri, C (2016)
With millions of people involved in collecting and treating recyclable products, waste recycling provides a critical entry point to an investigation of the spaces and dynamics of the Chinese economy. Based on sixteen months of in-depth ethnographic research, this thesis, 'Invisible spaces: variegated geographies of waste in China', describes and analyses waste and its boundaries, as well as the actors that deal with it at different scales within the country. The work examines how waste circulates, how it is regulated, and how it is represented in China. It presents stories of the people and places that configure the waste industry, and situates its analysis at the intersection of three different strands of literature: i) variegated capitalism; ii) informal economy; and iii) geographies of waste. The research contends that the 'afterlives' of goods are a productive prism which can be used to understand the variegated mode of capitalism in contemporary China and thus investigates the following question: to what extent do the different cultural, social, political, economic, and material dimensions of waste reveal the heterogeneous characteristics of Chinese capitalism? Central to my analysis is the concept of invisibility. I conceive invisibility as a socio- political process that brings about an uneven access to resources and labour for subaltern groups, as well as a relational concept encompassing the three complementary and dialectical dimensions of absolute, relative, and relational space. Invisibility is not only a metaphor to define the agency of informal workers, but also an allegory to describe the marginalisation of their activities and spaces. It is an asset and a curse, a condition and a strategy. These multiple dimensions make invisibility a productive device bringing to light the geographies of different accumulation regimes and everyday practices, as well as a potent tool to analyse the alternative representations of waste, value, labour, and development at play in contemporary China. With this in mind, the thesis engages with a number of important debates in geography. In particular, the five empirical chapters engage with literature on global production networks, labour geography, primitive accumulation, geographies of waste, and urban political ecology. While drawing these literatures into conversation with the variegated capitalism framework, the work suggests that the invisibility of waste activities is a powerful tool to analyse the nature and the mechanisms of the variegated modes of production in contemporary China.